2004
DOI: 10.1186/ar1190
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 120 IDDM = insulin-dependent diabetes mellitus; IFN = interferon; IL = interleukin; MS = multiple sclerosis; PCR = polymerase chain reaction; PBMC = peripheral blood mononuclear cell; RA = rheumatoid arthritis; SDA = Symbolic discriminant analysis; SLE = systemic lupus erythematosus; SLEDAI = SLE disease activity index. Arthritis Research & TherapyVol 6 No 3 Olsen et al. IntroductionThe relatively new technology of DNA microarrays has made it feasible to measure the expression levels of thousands of genes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 31 publications
(68 reference statements)
2
19
0
2
Order By: Relevance
“…By mediating disengagement of Ksr, Imp may interfere with Ksrinduced protection of the bowel mucosa, thereby permitting exacerbation of the inflammatory injury. Also, studies of gene profiles in peripheral blood mononuclear cells have shown that the expression of BRCA1, which is thought to associate with Imp, is down-regulated in families at risk for autoimmune diseases (54). Although the significance of this alteration is not clear, one may speculate that decreased expression of BRCA1 supports the interaction between Imp and Ksr and ultimately leads to the down-regulation of signal transduction in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…By mediating disengagement of Ksr, Imp may interfere with Ksrinduced protection of the bowel mucosa, thereby permitting exacerbation of the inflammatory injury. Also, studies of gene profiles in peripheral blood mononuclear cells have shown that the expression of BRCA1, which is thought to associate with Imp, is down-regulated in families at risk for autoimmune diseases (54). Although the significance of this alteration is not clear, one may speculate that decreased expression of BRCA1 supports the interaction between Imp and Ksr and ultimately leads to the down-regulation of signal transduction in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…While accumulation of versican during the inflammatory response can originate in the stromal connective tissue, a number of past as well as more recent studies have identified versican as a gene which is upregulated in monocytes in a number of pro-inflammatory states, such as myocardial infarction (Toeda et al, 2005), coronary stenosis (Wingrove et al, 2008), autoimmunity (Masuda et al, 2013; Olsen et al, 2004; Shou et al, 2006), and in response to pro-inflammatory stimulants such as lipopolysaccharide (LPS) (Lang et al, 2002) and hypoxia (Asplund et al, 2011; Asplund et al, 2009). In addition, the versican gene is differentially expressed in M1 macrophages, as opposed to M2 macrophages, as they differentiate from monocytes (Asplund et al, 2011; Martinez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Агенты, блокирующие TNFa, улучшают состояние больных РА, особенно в случае позитивности к АЦЦП, поэтому РА считается заболеванием, зависимым от TNFa [17]. При этом больные РА с более высокими уровнями синовиального воспаления и экспрессии TNFa в синовии [18], а также при увеличении экспрессии генов бета-рецептора IL2, SH2 домена 2А и GOS2 в периферической крови более чувствительны к блокаде TNFa [19].…”
Section: экспрессия фактора некроза опухолей альфа и интерферонов 1 тunclassified
“…Более того, изменения, происходящие в тканях и крови больных РА взаимосвязаны, поскольку показано, что в клетках крови больных РА повышена экспрессия генов, регулирующих морфогенез кости и хряща, по сравнению со здоровыми лицами [144] и отмечена корреляция экспрессии генов в крови и повреждённых тканях больных РА [145][146][147][148]. Ранее были выявлены различия в экспрессии ряда генов, ассоциированных с РЗ, по сравнению со здоровыми лицами не только в таргетных органах, но и в крови больных [17,[149][150][151].…”
Section: анализ экспрессии генов в крови как инструмент персонифицироunclassified